Appreciative Advising in Nursing Education. Issue 2 (March 2017) - Read, Aggie; Hicks, Jennifer; Christenbery, Tom
Abstract : The 6-phase Appreciative Advising framework for academic advising has been incorporated into a nursing program in the southeast United States, with promising initial results. Historical perspectives of academic advising, an overview of Appreciative Advising, and implementation of the framework are presented.